WEB-BASED TOURISM INFORMATION SYSTEM IN BUNGUS TELUK KABUNG SUB-DISTRICT OFFICE - vandra, rahul; Hadi, Harry Setya (JENTIK, 2024)
This system design aims to develop a web-based tourism information system for Bungus Teluk Kabung sub-district office and create applications that can be implemented in this sub-district office. This system research method is built on a website platform and runs online. The research method uses the system development life cycle (SDLC) with the waterfall model approach, which consists of 5 phases, namely: a) Analysis b) Design c) Implementation d) Maintenance e) Planning. The programming language used is (PHP), and the database application uses a data processor (MySql) as the database (RDBMS). The system design tools use Unified Modeling Language (UML) method with 4 (four) diagrams according to the design requirements, namely use case diagrams, activity diagrams, class diagrams and sequence diagrams. The tourism information application in the sub-district office of Bungus Teluk Kabung facilitates visitors to find information and tourist places in the study area. This system was tested and validated using the software testing method, using black box testing. This system can overcome the problems that exist in the area of Bungus Teluk Kabung sub-district.